Situation Report: Bulgaria, 21 January 1964 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Five Years for Spreading Jokes Economic Agreement with Soviet Union Scientific Delegation from the USSR Moldavian Party Visit Bulgarian Planning Committee Delegation in Yugoslavia Czechoslovak Economic Delegation Visit Trade with Ghana Bulgarian Economic Delegation in Uruguay Trade Delegation from North Korea